The Urgency Of Corruption Crimes In The Perspective Of Islamic Criminal Law - Nurhayati, Nurhayati (Legalpreneur Journal, 2023)
Corruption is an extraordinary crime and can even be categorized as an international crime. corruption has been categorized as a very serious crime and has an impact on the stability of a country. The fact is that despite the existence of corruption laws and money laundering laws in Indonesia, Corruption is increasing. Thus, this paper examines how corruption is assessed as a crime in the perspective of Islamic criminal law. The research was conducted by optimizing the literature data and secondary data review. This study shows that this corruption crime does not get a single discussion in Islamic law, but is likened to the act of theft, robbery or taking other people's things without permission.